Clinicoetiological Profile of Intrauterine Growth Restriction in Neonates Admitted at Teritiary Care Centre - D S, Darshana; Malwade, Sudhir; Kumar, Ganesh; Upadhyaya, Nidhi; Mane, Shailaja; Ali Khan, Md Owais; Maheswari, Abhinav (Journal of Neonatal Surgery, 2025)
Background:Intrauterine growth restriction (IUGR) is a significant contributor to neonatal morbidity and mortality, particularly in resource-limited settings. Understanding maternal and neonatal risk factors is essential for early intervention and improved neonatal outcomes. Methods:A cross-sectional study was conducted on 50 neonates diagnosed with IUGR and admitted to a tertiary care hospital's neonatal intensive care unit (NICU). Data on maternal risk factors, neonatal parameters, and outcomes, including morbidity and mortality, were collected and analyzed using SPSS version 23. Chi-square and logistic regression tests were applied to determine statistically significant associations. Results:Among the 50 IUGR infants, 10% died during hospital stay, while 26% were discharged with abnormal neurological findings. Hypoglycemia (36%) and perinatal asphyxia (30%) were the most frequent complications. Maternal malnutrition (30%) and anemia (36%) were significantly associated with neonatal mortality (p<0.05). Neonatal factors such as birth weight <2 kg, preterm status, and symmetrical IUGR were significantly associated with higher risk of mortality and morbidity.